A comparative analysis of multidimensional poverty in Sudan and South Sudan - Ballon, P; Duclos, J (Wiley, 2016)
This paper assesses multidimensional poverty in Sudan and South Sudan. We use the National Baseline Household Surveys of 2009 to measure poverty incidence in education, consumption, access to public assets and possession of private assets across these two countries. We differentiate between children aged 6 to 14 years and adults aged 15 years or older. We apply a counting method for measuring multidimensional poverty at the individual level and perform dominance tests to check for the robustness of the poverty comparisons. Our findings show regional and sub-population differences in the unidimensional and multidimensional poverty status of people in both countries. Poverty in Sudan is generally less severe than in South Sudan, with a pattern showing (1) lesser unidimensional incidence of poverty and (2) lower multidimensional poverty indices and prevalence, but similar breadth, both for adults and children. This pattern also points towards Khartoum and Western Equatoria as the states with the least poverty, and Northern Darfur, and Warap as the states with the greatest poverty, both for adults and children, in Sudan and South Sudan, respectively. Policy intended at reducing poverty in each of the two countries should recognize the poverty profile differences across age groups, geographical areas and dimensions.